The public R&D and productivity growth in Australia's broadacre agriculture: Is there a link? - Khan, F.; Salim, Ruhul; Bloch, Harry; Islam, N. (Blackwell Publishing Asia, 2017)
© 2017 Australian Agricultural and Resource Economics Society Inc.This paper investigates the dynamic relationships between research and development (R&D) expenditure and productivity growth in Australian broadacre agriculture using aggregate time series data for the period 1953 to 2009. The results show a cointegrating relationship between R&D and productivity growth and a unidirectional causality from R&D to TFP (total factor productivity) growth in Australian broadacre agriculture. Using the dynamic properties of the model, data from beyond the sample period are analysed by employing the variance decomposition and the impulse response function. The findings reveal that R&D can be readily linked to the variation in productivity growth beyond the sample period. Furthermore, the forecasting results indicate that a significant out-of-sample relationship exists between public R&D and productivity in broadacre agriculture.